FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBERIAN KOMPENSASI PADA KARYAWAN BANK - SUDARMIN MANIK (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2016)
Research themes are banks and financial institutions. The purpose of this study was to determine the factors that affect compensation in Bank Danamon Simpan Pinjam Unit Ps. Kota Duri. The populations in this study are employees of Bank Danamon Simpan Pinjam Unit Ps. Kota Duri which amounted to 32 people. Sampling was conducted using random sampling. The data analysis is done by using a reliability test, normality, F test, multiple linear regression R2 test and t test. The results showed that the independent variables affect compensation, with a value of correlation R = 0.999, which indicates a very strong relationship between productivity, ability to pay, willingness to pay, employee organizations and regulatory legislation with compensation. While the adjusted R-square in the can 0.997, which means productivity, ability to pay, willingness to pay, employee organizations and regulatory laws have contributed a contribution of 99.7% of the compensation.